2007
DOI: 10.5301/hip.2008.1892
|View full text |Cite
|
Sign up to set email alerts
|

The safety of hip injection with corticosteroid in the diagnosis and treatment of osteoarthritis

Abstract: Hip injection is safe provided a strict aseptic protocol is maintained. The time period of pain relief with hip injection is limited (average 2 months). For diagnostic purposes injections with local anaesthetic only is recommended. A large randomised control study would probably further substantiate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…24,25 Papavasiliou et al suggested that the rate of iatrogenic infection following an intra-articular corticosteroid injection may be increased in patients who later require an arthroplasty. 26 Although these findings were not corroborated by other studies, [27][28][29] caution is advised when contemplating an intra-articular corticosteroid injection that will provide shortterm symptomatic relief in a patient awaiting an elective arthroplasty. 22 The most common adverse effect of intra-articular corticosteroid injections is postinjection flare, a local increase in inflammation that develops within hours following the injection and can last 2 or 3 days.…”
Section: Potential Adverse Effects and Complicationsmentioning
confidence: 69%
“…24,25 Papavasiliou et al suggested that the rate of iatrogenic infection following an intra-articular corticosteroid injection may be increased in patients who later require an arthroplasty. 26 Although these findings were not corroborated by other studies, [27][28][29] caution is advised when contemplating an intra-articular corticosteroid injection that will provide shortterm symptomatic relief in a patient awaiting an elective arthroplasty. 22 The most common adverse effect of intra-articular corticosteroid injections is postinjection flare, a local increase in inflammation that develops within hours following the injection and can last 2 or 3 days.…”
Section: Potential Adverse Effects and Complicationsmentioning
confidence: 69%
“…In the early period, many retrospective studies reported no increased risks associated with IAI with regard to infection after subsequent THA. 6,[22][23][24][25][26][27][28] McIntosh et al 22 reported that there was no increased risk of PJI or SSI in a matched cohort study of 448 patients with THA performed within 1 yr after IAI. Chitre et al 23 reported no patient cases of PJI and one patient case of SSI in 36 patients who underwent THA at a mean of 18 mo following IAI.…”
Section: Outcomes Of Intraarticular Injections: Early Resultsmentioning
confidence: 99%
“…Chitre et al 23 reported no patient cases of PJI and one patient case of SSI in 36 patients who underwent THA at a mean of 18 mo following IAI. Karuppiah et al 24 reported no PJI or SSI in 128 patients who had undergone THA at a mean of 11 mo after IAI. Sreekumar et al 25 reported no PJI or SSI in 66 patients who underwent THA at a mean of 14 mo after IAI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patients undergoing joint replacement may be at increased risk for infection if they have surgery within the first 6 weeks after an injection [18]. However, this risk is still unclear because results of newer studies have shown that injection before replacement might be safer than previously reported [19,20]. The treating physician should communicate with the joint replacement surgeons, because they may have a particular preference regarding the timing of intra‐articular corticosteroids before joint replacement surgery.…”
Section: Specific Medicationsmentioning
confidence: 99%